1997
DOI: 10.1007/s002340050498
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous spinal epidural haematomas with repeated remission and relapse

Abstract: We present a case of spontaneous spinal epidural haematoma (SSEH) with a rare clinical course of repeated spontaneous recovery and relapse. The patient suffered three episodes of upper-back pain of sudden onset followed by sensory and motor dysfunction after weight lifting. In the first two episodes, the neurological deficits recovered spontaneously and completely. In the last episode, paraplegia persisted even after emergency surgery. Serial studies with computed tomographic (CT) myelography and magnetic reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 0 publications
1
22
0
Order By: Relevance
“…It has also been proposed that because the spinal cord segments T4–T8 have very few collateral channels and are usually supplied by only one artery, this makes them more vulnerable to ischemia [10]. Rarely, SSEH may recur [11]. …”
Section: Discussionmentioning
confidence: 99%
“…It has also been proposed that because the spinal cord segments T4–T8 have very few collateral channels and are usually supplied by only one artery, this makes them more vulnerable to ischemia [10]. Rarely, SSEH may recur [11]. …”
Section: Discussionmentioning
confidence: 99%
“…The possible etiological factors which have been reported in the literature with SSEH are coagulation disorders seven anticoagulant therapy, arteriovenous malformations, vasculitis, minor trauma, pregnancy, cavernous angiomas, Paget's disease, weight lifting, and hypertension. [2,4,5,10,11] These factors may cause secondary spinal epidural hematoma with a clear cause (60%) or SSEH of unclear cause (40%). [4,12,13] Analysis of a large series of cases of SSEH that was reported in the literature suggested correlation between SSEH and coexistence of arterial hypertension, [12] however, this correlation was again questioned in a recent publication.…”
Section: Discussionmentioning
confidence: 99%
“…This entity has been reported to be associated with blood dyscrasias, coagulopathy, anticoagulant treatment, infections, tumors, pregnancy vascular malformations, rheumatoid arthritis, Paget's disease, and rarely hypertension, however, no definite cause can be found in 40-50% of cases. [2][3][4][5] Although emergency surgical decompression is the recommended approach, [6,7] conservative management is advocated in the literature in few case reports if the patient has objective improvement in his neurological status early in the course of the disease. [6,8,9] We report our case which is unique in that the patient was detected to…”
Section: Introductionmentioning
confidence: 99%
“…20 Chen et al 21 reported a case where the patient had two episodes of spontaneous epidural hematoma treated conservatively. Unfortunately after the third episode the patient did not recover even after surgical decompression.…”
Section: Discussionmentioning
confidence: 99%